PEMANFAATAN WHATSAPP GROUP SEBAGAI MEDIA INFORMASI DAN KOMUNIKASI PENGAWAS DAN KEPALA SEKOLAH: TK WILAYAH KECAMATAN MAESAN - MATTALI MATTALI (Dewan Pendidikan Bondowoso, 2022)
School supervisors are tasked with supervising two important things in education in schools, namely the educational process and school management. The educational process is closely related to the activities of developing students' cognitive, affective and psychomotor potential. Meanwhile, school management is concerned with regulating the use of school resources effectively and efficiently. Principals and supervisors are responsible for fostering and supervising the course of the education process. Due to the important role of school supervisors and principals, information and communication media are needed that make it easier for supervisors and principals to collaborate. One of the most popular media today is Whatsapp. This research use desciptive qualitative approach. With this method, the researcher seeks to describe the phenomenon of supervision using Whatapps Group as a medium of information and communication to coordinate between supervisors and principals of the fostered kindergarten schools in Maesan sub-district. With the